Exploring the Nature of Compensation Strategies in Individuals With Dyslexia. (June 2018) - Gelbar, Nicholas W.; Bray, Melissa; Kehle, Thomas J.; Madaus, Joseph W.; Makel, Cheryl
Some individuals with developmental dyslexia are able to acquire age-appropriate reading comprehension abilities by the time they reach postsecondary education. This study explored the role that study strategies have with secondary students with dyslexia in achieving age-appropriate reading comprehension skills. The findings of this study indicated that study strategies were not significant predictors of reading comprehension abilities, though cognitive ability was a robust predictor. Furthermore, oral reading fluency was not a significant predictor. These findings further support that as words become more complex, oral reading fluency may not be related to reading comprehension. Practical implications and suggestions for future directions in this area are discussed.